Vascular invasion and lymph node metastasis mediate the effect of CA242 on prognosis in hilar cholangiocarcinoma patients after radical resection - Heng, Gang; Huang, Benqi; Shen, Yanbing; wang, Dan; Lan, Zhen; Yao, Yuxuan; Zhang, Jianxin; Jia, Jiankun; Zhang, Chengcheng (Frontiers in Oncology, 2022)
Background: Carbohydrate antigen 242 has been clinically used as a diagnostic biomarker for pancreatic cancer. However, the prognostic role of CA242 in hilar cholangiocarcinoma (HCCA) has not been identified. Also, it remains unclear to what extent the vascular invasion and lymph node metastasis mediates the effect of serum CA242 on prognosis. Objective: This study aimed to investigate whether vascular invasion and lymph node metastasis mediate the relationship between CA242 levels and clinical prognosis in HCCA patients after radical resection. Methods: Data of 234 HCCA patients who accepted radical resection from March 2008 to December 2014 were analyzed. Vascular invasion and lymph node metastasis were assessed by postoperative pathological examinations. Mediation analysis was performed to study the potential causal relationship between CA242 and overall survival (OS) and relapse-free survival (RFS). Survival analysis were performed using the Kaplan-Meier method. Results: Among 234 HCCA patients, 104 patients (44.4%) with normal CA242 levels (≤ 20 IU/ml) had significantly better OS (p=0.004) and RFS (p=0.001) than those 130 patients (55.6%) with elevated CA242 levels (>20 IU/ml). The logistic analysis showed that elevated CA242 was an independent risk factor for vascular invasion (p=0.006) and lymph nodes metastasis (p=0.040). The causal mediation analysis indicated that the vascular invasion (p=0.012 for OS; p=0.036 for RFS) and lymph nodes metastasis (p=0.024 for OS; p=0.014 for RFS) played significant roles in mediating the effect of serum CA242 on OS and RFS. Conclusion: Serum elevated CA242 could be a novel marker for prognosis prediction in HCCA patients. Vascular invasion and lymph node metastasis mediated the relationship between CA242 and clinical prognosis. Key words: CA242; Vascular invasion; Lymph nodes metastasis; Mediation analysis